Reading the Gospels with Karl Barth - Migliore, Daniel L. (Wm. B. Eerdmans Publishing Co., 2017)
Intro -- Title Page -- Copyright -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- 1. The Election of Grace -- 2. Revelatory Word or Beloved Son? -- 3. The Gospel within the Commandment -- 4. A Rich Disciple? -- 5. The Compassion of Jesus Christ -- 6. The Journey of God's Son -- 7. Parabolic Retelling and Christological Discourse -- 8. The Riddle of Gethsemane -- 9. The Passion of God Himself -- 10. The Self-Witness of the Risen Jesus -- 11. The Sum of the Gospel -- 12. What's in Those Lamps? -- Contributors -- Index of Authors -- Index of Subjects -- Index of Scripture References.